The invisible forces of knowledge sharing. - Ng, Chan Yuan. (2008)
The aim of this study is to examine the relationship between knowledge sharing and organizational justice and trust in an organization. In addition, different social networks were mapped out for better understanding of knowledge sharing in an organization.